Greenland, view of Kjerulf Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. Junction of streams of right and left valleys. In background (extreme left) is sloping side of innermost southern point of mountain range forming the eastern side of Kjerulfs [Kjerulf] Fjord, from its entrance at Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord] to the point where it forms the eastern (left side looking up) side of Left Valley and in this photo it is seen curving E.N.E. to disappear around to the left and (beyond here) forms the north side of Dickson [Dicksons] Fjord. In background L.A.B.'s Scoop Mt. [Mountain] and the range of mts. [mountains] which here form the eastern side of Hisinger Glacier [Hisinger Gletscher]. This is the northern most point of this range. To the left the range runs to the east and forms the south side of Dickson [Dicksons] Fjord. In background stream of Left Valley; foreground stream of Right Valley.